2001
DOI: 10.1148/radiology.218.1.r01ja44127
|View full text |Cite
|
Sign up to set email alerts
|

Superior Labral Anterior Posterior (SLAP) Lesions of the Glenoid Labrum: Reliability and Accuracy of MR Arthrography for Diagnosis

Abstract: MR arthrography of the shoulder is reliable and accurate for detection of SLAP tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
81
1
8

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(100 citation statements)
references
References 17 publications
10
81
1
8
Order By: Relevance
“…Again, this may be related to the particular surgical technique, arthroscopic criteria, or patient population associated with this particular site. Several studies have reported that the use of intraarticular contrast improves the diagnostic capabilities of MR imaging for the glenoid labrum when compared to conventional MR imaging (7,15,16,(32)(33)(34)(35)(36). Therefore, the possibility exists that MR arthrography performed with the extremity MR system may result in increased sensitivity and specificity for tears of the glenoid labrum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, this may be related to the particular surgical technique, arthroscopic criteria, or patient population associated with this particular site. Several studies have reported that the use of intraarticular contrast improves the diagnostic capabilities of MR imaging for the glenoid labrum when compared to conventional MR imaging (7,15,16,(32)(33)(34)(35)(36). Therefore, the possibility exists that MR arthrography performed with the extremity MR system may result in increased sensitivity and specificity for tears of the glenoid labrum.…”
Section: Discussionmentioning
confidence: 99%
“…MAGNETIC RESONANCE (MR) IMAGING is regarded as a useful and accurate technique for diagnosing shoulder disorders, including rotator cuff disease and lesions of the glenoid labrum (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). MR imaging of the shoulder has been predominantly performed by using wholebody MR systems operating at high-field-strengths (1.0 -1.5 Tesla) or, more recently, utilizing low-fieldstrength (0.2-0.35 Tesla) scanners (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For MRA, these values increased to 75 and 80 percent [30]. As already discussed, the differentiation between types I, III, and IV SLAP tears can also be problematic, with important consequences for the planning of surgery [28].…”
Section: Diagnosismentioning
confidence: 89%
“…These tears, which are highly associated with rotator cuff lesions [4], are considered of low clinical relevance [27] and surgery for these patients may not be indicated [28]. However, type I SLAP tears are difficult to distinguish from type III and type IV preoperatively [28]. Consequently, inaccurate diagnosis can result in unnecessary arthroscopy.…”
Section: Lesions Of the Glenoid Labrummentioning
confidence: 99%